Ballad of the Buried Life - Hagelstange, Rudolf (University of North Carolina studies in the Germanic languages and literatures ;, 2020)
A news item concerning six German soldiers trapped for years in the army food storage bunker provided Rudolf Hagelstange with a plot and an effective symbol to express the tensions, emotions, and paradoxes of modern man's being. In this volume the poet Herman Salinger translates Hagelstange's poem into verse with the original German on facing pages. An introductory essay by Charles W. Hoffmann gives context on Hagelstange and the ballad.